2006
DOI: 10.1016/j.schres.2006.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and psychosis: Links between depression, self-esteem, negative schematic beliefs and delusions and hallucinations

Abstract: This study provides evidence for the role of emotion in schizophrenia spectrum-disorders. Mood, self-esteem and negative evaluative beliefs should be considered when conceptualising psychosis and designing interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
252
4
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(297 citation statements)
references
References 34 publications
30
252
4
11
Order By: Relevance
“…Fowler et al (2006) found that a sample of 252 people with psychosis endorsed significantly more negative schematic beliefs both about self and about others than a non-clinical control group. In a related study, employing an overlapping sample, Smith et al (2006) found, among a sample of 100 psychosis patients, that those endorsing more negative beliefs about self and others had persecutory delusions of greater severity and were more preoccupied and more distressed by them than those endorsing less negative beliefs. Fowler et al (2011) extended these cross-sectional findings, using structural equation modelling to examine the longitudinal relationships between negative cognition, depression and paranoia over a year in 301 people with psychosis.…”
Section: Schematic Beliefsmentioning
confidence: 96%
See 1 more Smart Citation
“…Fowler et al (2006) found that a sample of 252 people with psychosis endorsed significantly more negative schematic beliefs both about self and about others than a non-clinical control group. In a related study, employing an overlapping sample, Smith et al (2006) found, among a sample of 100 psychosis patients, that those endorsing more negative beliefs about self and others had persecutory delusions of greater severity and were more preoccupied and more distressed by them than those endorsing less negative beliefs. Fowler et al (2011) extended these cross-sectional findings, using structural equation modelling to examine the longitudinal relationships between negative cognition, depression and paranoia over a year in 301 people with psychosis.…”
Section: Schematic Beliefsmentioning
confidence: 96%
“…Freeman, Garety and Kuipers (2001) reported that 80% of a group of people with persecutory delusions showed significant levels of depression, with an overall mean BDI score of 23. Smith et al (2006) found that, among a sample of 100 recently-relapsed people with a schizophrenia spectrum diagnosis, those who were more depressed experienced persecutory delusions of greater severity and were more preoccupied and distressed by them. Bentall et al's (2009) large transdiagnostic study used structural equation modelling with a mixed group of people with psychosis and/or depression to show that pessimistic thinking and negative emotion had a significant association with paranoia, even when executive functioning and reasoning styles were controlled for.…”
Section: Depression and Positive Symptomsmentioning
confidence: 99%
“…35,36 Next, we averaged diffusion parameters across each cluster ROI. We used STATA software version 13.1 (StataCorp) for regression analyses comprising the ordered probit model 37 and repeated-measures analysis of variance (ANOVA). Progressive changes in cluster ROIs were analyzed using repeatedmeasures ANOVA.…”
Section: Voxelwise Statistical Analysesmentioning
confidence: 99%
“…We used ordinal regression analyses because our hypothesis specifically implied associations with the PANSS positive subscore, consisting of 7 ordinal variables. 37 Additional DTI parameters, MD, λ 1 , and λ 23, were extracted from identified cluster ROIs and used only in secondary analyses to explore which parameters were driving any significant FA changes.…”
Section: Voxelwise Statistical Analysesmentioning
confidence: 99%
“…Barrowclough et al (2003) found that schizophrenia patients with a negative selfevaluation scored higher on the positive symptoms subscale measuring hallucinations and delusions. Smith et al (2006) examined patients who suffered relapses in psychosis and showed that those with worse depression, self-esteem, and negative beliefs, had persecutory delusions of greater severity. In healthy participants, two longitudinal studies reported that psychosis-prone individuals had a higher rate of Major Depressive Disorder than controls (Chapman et al, 1994;Kwapil et al, 1997) and were at a higher risk to develop an incident depression .…”
Section: Introductionmentioning
confidence: 99%